Egzemplifikacja i kategoryzacja innowacji na rynku owoców i produktów owocowych w Polsce - Rakowska, Joanna (Zeszyty Naukowe SGGW - Ekonomika i Organizacja Gospodarki Żywnościowej, 2010)
The research aimed at making an inventory of recent and ongoing fruit market and fruit product innovations and at assessing what new or improved features they offer, and whether consumers are able to identify and/or recognise them. The list of innovations obtained has been coded, categorised, sorted, and reduced in subsequent stages. First, the examples received were categorised according to the Oslo Manual definitions. Second, product and marketing innovations were selected, as they are the only ones that were likely to be recognised by consumers. Next, the analysis revealed that the novelties these innovations offered related to Convenience, Health, Differentiation, Target Group, Information, Sensory Characteristics, In Home and/or Out of Home and Quality. Some innovations offered only one novel aspect, whereas others offered multiple aspects. Interrelationships between novel aspects are discussed for those innovations that offered a combination of aspects.